Should we screen for osteoporosis using calcaneal ultrasound?. Issue 3 (March 2015) - Silakoski, Jenna; Williams, Aaron
Abstract : Evidence‐Based Answer : Calcaneal ultrasound should not be used to screen for osteoporosis because of the wide variation in sensitivity and specificity. Further research is needed to determine the correlation between dual energy X‐ray absorptiometry (DEXA) scan and calcaneal ultrasound for osteoporosis screening or diagnosis (SOR: B, systematic review of cohort trials).